Waste cigarette butt-derived nitrogen-doped porous carbon as a non-mercury catalyst for acetylene hydrochlorination. (6th October 2021) - Jin, Xin; Hao, Yalei; Liu, Chengxiang; Feng, Hongbin; Li, Xingyun; Zhu, Yan; Zhou, Yuxin; Song, Yujiang; Hu, Jiapeng
Abstract : The development of advanced carbon materials as metal-free catalysts holds great importance for mercury catalyst replacement in acetylene hydrochlorination. Abstract : The development of advanced carbon materials as metal-free catalysts holds great importance for mercury catalyst replacement in acetylene hydrochlorination. In this paper, we transform discarded cigarette butts into a porous nitrogen-doped carbon material (N-CB-800), exhibiting characteristics of high specific surface area, large N doping amount, defective structure and strong C2 H2 chemical adsorption ability. These unique features endow N-CB-800 with a high catalytic performance with an acetylene conversion of 71.8% at 220 °C and an acetylene space velocity of 100 h −1, making it one of the most active metal-free catalysts. This work will be of great value for the recycling of living waste and provide meaningful guidance for the development of non-mercury catalysts for acetylene hydrochlorination.